Institutional Strengthening of Ornamental Plant Farmer Groups Post COVID-19 Pandemic in Bogor Regency: SEM-PLS Analysis: Penguatan Kelembagaan Kelompok Tani Tanaman Hias Pascapandemi Covid-19 di Kabupaten Bogor: Analisis SEM-PLS - Pepi Rospina; Ludivica Endang Setijorini; Ismail Hasvi; Wien Kuntari (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabaya, 2026)
The COVID-19 pandemic encouraged people to take up new hobbies, including cultivating ornamental plants at home. This study analyzed the level of institutional strengthening of ornamental plant farmer groups in Bogor Regency, identified the factors that significantly influence it, and formulated post-pandemic strategies. Using an explanatory sequential mixed-method design, the study involved 54 respondents from three sub-districts (Gunungsindur, Cijeruk, and Tamansari) quantitative analysis using SEM-PLS (SmartPLS 4) was complemented by in-depth interviews to deepen the interpretation of the quantitative findings. On average, respondents were 42 years old, had junior to senior secondary education, around eight years of farming experience, and managed 447 m² of land. Farmer innovativeness was moderate, whereas media exposure remained low. The initial model (Model 1) indicated that environmental factors and farmer group role jointly influenced institutional strengthening (Y1 = 0.097X2 + 0.664X3; R² = 49.1%). After trimming the non-significant environmental factor, the final model showed that farmer group role was the only significant predictor (path coefficient = 0.699; R² = 48.9%). Post-pandemic interventions should therefore prioritize strengthening farmer group roles to enhance group capacity and member capacity.